PENINGKATAN HASIL BELAJAR MATERI BANGUN DATAR MELALUI MODEL TEAM ASSISTED INDIVIDUALIZATION DI KELAS IV B SD NEGERI 47 KOTA JAMBI - Heni Maladewi (Jurnal Pesona Dasar, 2019)
To be able to learn something well, we need to hear, see, ask questions about it, and discuss it with others. Not only that, students need to "do it", which is describing something in their own way, showing examples, trying to practice skills and doing tasks that demand the knowledge they have gained. This research addressed the question: Is the Team Assisted Individualization model able to improve students’ learning outcomes in mathematics? While the purpose of this study was to find out how far the implementation of the Team Assisted Individualization model can improve Mathematics in the topic of Flat Surfaces learning outcomes in class IV B. This research uses two rounds of action research. Each round consists of four stages, namely: design, activity and observation, reflection, and revision. The target of this study is class IV B. The data obtained are in the form of formative test results, observation sheets of teaching and learning activities. From the results of the analysis it was found that student learning outcomes experienced an increase from the first cycle to the second cycle, namely, the first cycle (80.64) and the second cycle (87.09%) The conclusion of this study is that the Team Assisted Individualization model can have a positive effect on the learning outcomes of Jambi City Elementary School 47 students, and this learning model can be used as an alternative in mathematics learning.